The role of neutrophils in Brucellosis - BARQUERO-CALVO, ELIAS (2020)
Brucellosis is a bacterial disease of domestic animals and humans. The pathogenic ability of Brucella organisms relies on their stealthy strategy and their capacity to replicate within host cells and to induce long-lasting infections. Brucella organisms barely induce neutrophil activation and survive within these leukocytes by resisting microbicidal mechanisms. Very few Brucella-infected neutrophils are found in the target organs, except for the bone marrow, early in infection. Still, Brucella induces a mild reactive oxygen species formation and, through its lipopolysaccharide, promotes the premature death of neutrophils, which release chemokines and express “eat me” si nals. This effect drives the phagocytosis of infected neutrophils by mononuclear cells that become thoroughly susceptible to Brucella replication and vehicles for bacterial dispersion. The premature death of the infected neutrophils proceeds without NETosis, necrosis/oncosis, or classical apoptosis morphology. In the absence of neutrophils, the Th1 response exacerbates and promotes bacterial removal, indicating that Brucella-infected neutrophils dampen adaptive immunity. This modulatory effect opens a window for bacterial dispersion in host tissues before adaptive immunity becomes fully activated. However, the hyperactivation of immunity is not without a price, since neutropenic Brucella-infected animals develop cachexia in the early phases of the disease. The delay in the immunological response seems a sine qua non requirement for the development of long-lasting brucellosis. This property may be shared with other pathogenic alphaproteobacteria closely related to Brucella. We propose a model in which Brucella-infected polymorphonuclear neutrophils (PMNs) function as “Trojan horse” vehicles for bacterial dispersal and as modulators of the Th1 adaptive immunity in infection.